Bean genotypes ability of fixing N2 - Pereira, Pedro Antonio Arraes; Araujo, Ricardo Silva; Rocha, Ricardo Eiras Moreira da; Steinmetz, Silvio (Pesquisa Agropecuaria Brasileira, 2014)
A field screening program was conducted to evaluate the ability of several bean (Phaseolus vulgaris L.) genotypes to fix nitrogen biologically. Dry weight of nodules and nitrogenase activity were found to be highly variable. They were, higher at the flowering stage than at the middle pod-filling stage of bean plants. These results demonstrated that a senescence of the nodules occurred at this physiological phase. On the other hand, more than 40% of the genotypes studied showed nodule masses higher than 92,5 mg pl-1, (dry weight of nodules). In addition, some genotypes showed as high as 200 mg pl-1 , which in turn can be compared to nodule masses obtained from other leguminous plants that are know to have efficient symbioses with bacteria of the genus Rhizobium. CNF 1855, CNF 1882 and Valle 18 were the best nodulating genotypes while CNF 1454, Lustroso Claro, Mulatinho and CNF 402 were some of the worst ones.
Keywords: Phaseolus vulgaris; nodulation; variability; N2 fixation